2010
DOI: 10.1177/1933719109348028
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Aging is Associated With Altered Gene Expression in Human Luteinized Granulosa Cells

Abstract: Declining reproductive success with aging is attributable to qualitative and quantitative deterioration in oocytes, which are nurtured by granulosa cells (GCs). This prospective study assesses whether reproductive aging is accompanied by differential gene expression in luteinized GCs from in vitro fertilization (IVF) patients. Women with nonovarian infertility etiologies were categorized as younger (< or =30, n = 3) or older (> or =40, n = 3). During oocyte retrieval, mural GCs were isolated; messenger RNA (mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…A likely explanation for this result is that here investigated GCs were exposed to hCG in vivo. As shown by us and others (Murphy 2000, Hurwitz et al 2010, Jeppesen et al 2012, McReynolds et al 2012, hCG administration causes luteinization of GCs, and a changing physiological and molecular signatures. Therefore, it is possible that hCG administration changes cell sensitivity of the FSH response.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A likely explanation for this result is that here investigated GCs were exposed to hCG in vivo. As shown by us and others (Murphy 2000, Hurwitz et al 2010, Jeppesen et al 2012, McReynolds et al 2012, hCG administration causes luteinization of GCs, and a changing physiological and molecular signatures. Therefore, it is possible that hCG administration changes cell sensitivity of the FSH response.…”
Section: Discussionmentioning
confidence: 74%
“…Although numerous studies have documented the relationship between poor oocyte quality and GC abnormalities in human and animals (Buccione et al 1990, Senbon et al 2003, Assou et al 2012, Huang & Wells 2012, Matsuda et al 2012, effects of age on physiological function and molecular signature of GCs have so far been only sparsely investigated. Indeed, to our knowledge, they have never before been performed in such distinct age groupings (Hurwitz et al 2010, McReynolds et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Although granulosa cells for these two studies were obtained from superstimulated follicles (by-passing the natural selection process), they still provide some useful insights about the cellular mechanisms in maternal reproductive aging. Likewise, down-regulation of IL-1 and IL-6 gene families in luteinized granulosa cells from patients of advancing age (Hurwitz et al, 2010) may partly explain the age-associated luteal dysfunctions.…”
Section: Transcriptome Of Dominant Follicles During Maternal Agingmentioning
confidence: 95%
“…Oocyte growth is supported by surrounding granulosa cells [17], and a deterioration in the characteristics of these granulosa cells derived from full-grown antral follicles have been observed in aged women and cows [18][19][20][21]. Result from real time RT-PCR experiments have revealed that the expression of some genes including those that encode for antioxidants in mouse ovary was affected by aging [22].…”
Section: Introductionmentioning
confidence: 99%